Blood M2a monocyte polarization and increased formyl peptide receptor 1 expression are associated with progression from latent tuberculosis infection to active pulmonary tuberculosis disease. (December 2020) - Chen, Yung-Che; Chang, Yu-Ping; Hsiao, Chang-Chun; Wu, Chao-Chien; Wang, Yi-Hsi; Chao, Tung-Ying; Leung, Sum-Yee; Fang, Wen-Feng; Lee, Chiu-Ping; Wang, Ting-Ya; Hsu, Po-Yuan; Lin, Meng-Chih
Highlights: No known biomarkers for progression from latent to active tuberculosis. Blood monocyte M2a polarization in active tuberculosis disease. Formyl peptide receptor 1 upregulation on M1 in active tuberculosis disease. M2a polarization of THP-1 cells to Mycobacterium tuberculosis- specific antigens. Abstract: Objectives: This study aims to explore the role of M2a polarization and formyl peptide receptor (FPR) regulation in the reactivation of Mycobacterium tuberculosis ( Mtb ) infection. Methods: M1/M2a monocyte percentage and FPR1/2/3 protein expression of blood immune cells were measured in 38 patients with sputum culture (+) active pulmonary TB disease, 18 subjects with latent TB infection (LTBI), and 28 noninfected healthy subjects (NIHS) using flow cytometry method. Results: M1 percentage was decreased in active TB versus either NIHS or LTBI group, while M2a percentage and M2a/M1 percentage ratio were increased. FPR1 expression on M1/M2a, FPR2 expression on M1, and FPR3 expression of M1 were all decreased in active TB versus LTBI group, while FPR1 over FPR2 expression ratio on NK T cell was increased in active TB versus either NIHS or LTBI group. In 11 patients with active TB disease, M1 percentage became normal again after anti-TB treatment. In vitro Mtb -specific antigen stimulation of monocytic THP-1 cells resulted in M2a polarization in association with increased FPR2 expression on M2a. Conclusions: Increased M2a and decreased M1 phenotypes of blood monocyte may serve as a marker for active TB disease, while decreased FPR1 on blood monocyte may indicate LTBI status.